Relationship Between E-Government, E-Participation, Human Development, and Its Effect on Democracy in Asia - Raharja, Jaka; Qodir, Zuly (Journal of Government and Civil Society, 2024)
This research explores the relationship between E-Government, E-Participation, Human Development, and their influence on peace in Asia. The purpose of this study is to uncover how the implementation of E-Government and the level of E-Participation affect Human Development, how Human Development impacts democracy, and how the third variable influences democracy in Asian countries. This study uses a quantitative approach and analyzes data from various reports to examine the construction of E-Government, E-Participation, Human Development, and Democracy using Smart Pls 3. The results of the study indicate that there is a positive and significant influence between E-government and E-Participation, secondly, E-Government does not affect Human Development. Third, Human Development influences Democracy positively and significantly. Fourth, E-government through Human Development does not affect Democracy, but E-Participation through Human Development influences democracy positively and significantly.Penelitian ini mengeksplorasi hubungan antara E-Government, E-Participation, Human Development, dan pengaruhnya terhadap demokrasi di Asia. Tujuan dari penelitian ini adalah untuk menyelidiki bagaimana penerapan E-Government dan tingkat E-Participation mempengaruhi Pembangunan Manusia, dan selanjutnya, bagaimana Pembangunan Manusia berdampak pada demokrasi serta bagaimana pengaruh ketiga variabel terhadap demokrasi di negara-negara Asia. Studi ini menggunakan pendekatan kuantitatif, menganalisis data dari berbagai laporan untuk mengkaji konstruksi E-Government, E-Participation, Human Development, dan Democracy menggunakan Smart Pls 3. Hasil penelitian menunjukkan ada pengaruh yang positif dan signifikan antara E-government dengan E-Participation, kedua E-Governemnt tidak mempengaruhi Human Development. Ketiga, Human Development mempengaruhi Demokrasi secara positif dan signifikan. Keempat, E government melalui Human Development tidak mempengaruhi Demokrasi, tetapi E-Participation melalui Human Development mempengaruhi demokrasi secara positif dan signifikan.